Sports math an introductory course in the mathematics of sports science and sports analytics - Minton, Roland B. 1956- (Boca Raton, FL CRC Press, Taylor & Francis Group, 2017)
"This is a textbook for a course in sports science or sports analytics. The opening section is on standard mathematical sports examples which are physics-related, including projectile motion and rotational motion. A middle section introduces several rating systems. Many of these matrix-based systems were made famous by the soon-defunct college football BCS system. The final section of the book contains statistical analysis of sports, taking in Moneyball-like techniques. Game strategies and player evaluation are the main goals of these chapters."--Provided by publisher.
Projectile motion -- Rotational motion -- Sports illusions -- Collisions -- Rating systems -- Voting systems -- Saber- and other metrics -- Randomness in sports -- Sports strategies -- Big data and beyond.
Ms. Cherrylyn Alota (Recommending faculty) - Bookfair 2019
Includes bibliographical references and index.
Keywords: Sports -- Mathematics